PENGARUH MOTIVASI TERHADAP PRESTASI BELAJAR MAHASISWA MANAJEMEN INFORMATICS & BUSINESS INSTITUTE DARMAJAYA LAMPUNG - Anggalia Wibasuri; Addriansyah - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2014)
Education isone of the requirement simproving the quality of human resources developmentgoals. Informatics & Business Institute Darmajaya Lampung is a vehicle for improving the quality ofhuman resources. Successin learning can be affected by many factors, one of which is motivation,motivationto foster the spirit of learning so that students are motivated and happy to do the act oflearning. Student learning motivation Informatics & Business Management Institute DarmajayaLampung not optimal inlectures, judging from the large number of students who have not reached2.75 at 51%. This study aimed tomeasure the influence of motivation on student achievementInformatics & Business Management Institute Darmajaya Lampung.The study population wasall the management students of class of 2009, 2010 and 2011during the year 2012 at the Institute of Informatics & Business Lampung Darmajaya of 588 studentswho subs equently obtained a sample of 85 respondents. Hypothesis testing results obtainedamounted to 3,741t value > table 1.664. Motivation means significantly influence studentachievement Informatics & Business Management Institute Darmajaya Lampung. The coefficient ofdetermination value generating the value of r Square of 0.144 indicates that student achievementInformatics & Business Management Institute Darmajaya Lampung influenced by the motivation of14.4%.